Predicting Outcome in Persistent Pulmonary Hypertension of the Newborn with Score for Neonatal Acute Physiology- Version II (SNAP-II) - Nguyen Huu Hieu; Tran Minh Dien; Le Thi Ha (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2021)
Persistent pulmonary hypertension of the Newborn is a serious disease related to the adaptation of fetal circulation after birth. This study aims to determine the ability of Score for Neonatal Acute Physiology- version II (SNAP-II) for predicting outcome in neonates with persistent pulmonary hypertension of the newborn (PPHN). This prospective cohort study of 52 neonates with PPHN was carried out in the Neonatal Center and Surgical Intensive Care Unit, Vietnam National Children’s Hospital over a period of 7 months (10/2020 to 4/2021). SNAP-II score was evaluated within the first 12 hours of admission. Outcome of treatment was recorded at the 28th day of treatment. The study results show that the mortality rate was 25.0%; 11.5% of the patients had to use ventilators; 28.8% of the patients used NO inhalers and 9;6% of the patients required ECMO. SNAP-II score has the power of predicting mortality in PPHN with the area under the ROC curve of 0.76 (95% CI: 0.61- 092, p < 0.05). SNAP-II score ≥ 27 was calculated as cutoff for predicting mortality with the sensitivity of 92;3% and specificity of 53.8%. Each point increase in SNAP-II score increased the odd of mortality by 1.10 (95% CI: 1.03- 1.18, p< 0.05). SNAP-II score also has the ability of predicting secondary outcome of PPHN: using ECMO (AUC 0.81). Notably, this study finds that the SNAP-II scoring system is a useful and reliable tool to predict mortality of neonates with PPHN and to assess the need of ECMO therapy. Keywords: Persistent pulmonary hypertension of the newborn, Score for Neonatal Acute Physiology- version II, neonatal mortality. References [1] J. Nair, S. Lakshminrusimha, Update on PPHN: Mechanisms and Treatment, Seminars in Perinatology, Vol. 38, No. 2, 2014, pp. 78-91, https://doi.org/10.1053/j.semperi.2013.11.004.[2] M. A. Steurer, R. J. Baer, S. Oltman, K. K. Ryckman, S. K. Feuer, E. Rogers, R. L. Keller, L. Jelliffe- Pawlowski, Morbidity of Persistent Pulmonary Hypertension of the Newborn in The First Year of Life, Journal of Pediatric, Vol. 213, 2019, pp. 58-65, https://doi.org/10.1016/j.jpeds.2019.06.053.[3] N. Nakwan, N. Nakwan, J. Wannaro, Predicting Mortality in Infants with Persistent Pulmonary Hypertension of the Newborn with The Score for Neonatal Acute Physiology-Version II (SNAP-II) in Thai Neonates, Journal of Perinatal Medicine, Vol. 39, No. 3, 2011, pp. 311-315, https://doi.org/10.1515/jpm.2011.011.[4] D. K. Richardson, J. D. Corcoran, G. J. Escobar, G. J. Escobar, S. K. Lee, SNAP-II and SNAPPE-II: Simplified Newborn Illness Severity and Mortality Risk Scores, The Journal of pediatrics, Vol. 138, No. 1, 2001, pp. 92-100, https://doi.org/10.1067/mpd.2001.109608.[5] S. Sardar, S. Pal, R. Mishra, A Retrospective Study on The Profile of Persistent Pulmonary Hypertension of Newborn in A Tertiary Care Unit of Eastern India, Journal of Clinical Neonatology, Vol. 9, No. 1, 2020, pp. 18-26, https://doi.org/10.4103/jcn.JCN_68_19.[6] M. Sauthier, L. Rose, P. Jouvet, Pediatric Prolonged Mechanical Ventilation: Considerations for Definitional Criteria, Respiratory care, Vol. 62, No. 1 2017, pp. 49-53, https://doi.org/10.4187/respcare.04881.[7] M. N. M. Bah, R. Y. H. Tan, H. Razak, M. H. Sapian, N. Abdullah, E. Y. Alias, Survival and Associated Risk Factors for Mortality among Infants with Persistent Pulmonary Hypertension of The Newborn in Malaysia, Journal of Perinatology, Vol. 41, 2021, pp. 786-793, https://doi.org/10.1038/s41372-021-00962-6.[8] E. D. Skarsgard, Y.C. MacNab, Z. Qiu, R. Little, S. K. Lee, SNAP-II Predicts Mortality among Infants with Congenital Diaphragmatic Hernia. Journal of Perinatology, Vol. 25, No. 5, 2005, pp. 315-319, https://doi.org/10.1038/sj.jp.7211257.[9] L. Y. Chien, R. Whyte, P. Thiessen, R. Walker, D. Brabyn, S. K. Lee, SNAP-II Predicts Severe Intraventricular Hemorrhage and Chronic Lung Disease in The Neonatal Intensive Care Unit, Journal of Perinatology, Vol. 22, No. 1, 2002, pp. 26-30, https://doi.org/10.1038/sj.jp.7210585.[10] S. Jaroensri, W. Kamolvisit, N. Nakwan, Risk Factor Analysis of Pneumothorax Associated with Persistent Pulmonary Hypertension of The Newborn in Thai Neonates, The Journal of Maternal-Fetal & Neonatal Medicine, Vol. 33, No. 24, 2020, pp. 4090-4095, https://doi.org/10.1080/14767058.2019.1596403.[11] F. Kipfmueller, L. Schroeder, T. Melaku, A. Geipel, C. Berg, U. Gembruch, A. Heydweiller, C. Bendixen, H. Reutter, Prediction of ECMO and Mortality in Neonates with Congenital Diaphragmatic Hernia Using The SNAP-II Score, Klinische Pädiatrie, Vol. 231, No. 6, 2019, pp. 297-303, https://doi.org/10.1055/a-1009-6671.